Impulsivity, suicidal thoughts, psychological distress, and religiosity in adolescents and young adults - Abdullah, Mudassar; Khalily, Muhammad Tahir; Ruocco, Anthony Charles; Hallahan, Brian (Frontiers in Psychiatry, 2023)
Background Impulsivity is associated with suicidal acts and ideation, whereas higher religious commitment has been identified as a potential protective factor linked to lower suicidal ideation. Objectives We examined the extent to which higher religious commitment is associated with lower suicidal ideation and whether religious commitment modifies the relationship between impulsivity and suicidal ideation. Methods Adolescent and young adult males, with a prior history of suicidal act and ideations, completed standardized questionnaires [i.e., Beck Scale for Suicidal Ideation (BSS), Barratt Impulsivity Scale-II (BIS-II), Depression Anxiety Stress Scale (DASS), and Religious Commitment Inventory-10 (RCI-10)], to assess impulsivity, suicidal ideation, distress, and religious commitment. Regression and mediation analyses were performed to investigate the relationships among impulsivity, religious commitment, and suicidal ideation. Results Of the 747 study participants (mean age 18.8 years, SD = 4.1), 151 (20.2%) had a history of suicidal acts and 177 (23.7%) had a history of suicidal ideation. Non-planning impulsivity (predictor) was inversely associated with religious commitment (r = −0.33, p < 0.01), and religious commitment (mediator) was inversely related to suicidal ideation (outcome) (r = −0.32, p < 0.01). These findings remained statistically significant when controlling for either religious commitment or non-planning impulsivity, as appropriate. Higher religious commitment reduced the association between non-planning impulsivity and suicidal ideation (p < 0.01). Conclusion The findings highlight the potential for cultivating spirituality to buffer against higher suicidal ideation, and thus could be considered as an additional therapeutic strategy for individuals with higher levels of impulsivity and co-morbid suicidal ideation.